Empowering the Farmers of India: a case study of e-choupal in Uttarakhand - M.A. Ansari,; Ajay Kumar Yogeshwar, (Journal of Agricultural Extension Management, 2025)
Agriculture has been and continues to be the backbone of the Indian economy as it contributes around 20 per cent to its GDP and about 70 per cent of the population is engaged in the agriculture sector. Although Green Revolution made the country self sufficient in the production of food grains, the recent stagnation, rather deceleration in agricultural production, has sent alarm bells ringing in the ears of our policy makers. In a globally competitive agrarian economy, Indian agriculture has to change its rationale and strategy to meet the expectations of a billion-plus population in the 21st century. This necessitates a paradigm shift in the perception of agriculture from 'mere subsistence level' to a market-led and demand-driven enterprise. In the prevailing technology environment, information has emerged as a key factor in the process of agricultural production. The premium placed on 'knowledge' in the contemporary society has led the policymaking in agriculture into a new domain. Knowledge networking is being promoted through various initiatives driven by Information and Communication Technologies (ICTs) leading to info-tech empowerment of the farming community